Lifelong learning, policy development and practice: a case study of the Republic of Ireland - Doona, Anne (2007)
The aim of this thesis is to study lifelong learning policy development in the Republic of Ireland and its translation into practice in Third Level Institutions. The specific purpose of the study is to map the development of policy and investigate the influences on this development including the changing socio economic and political context within Ireland and its membership of the European Union. The focus of the research is also Learning for Life, the Irish government's major White Paper on adult education and lifelong learning, published in 2000. The research also begins to investigate how Third Level Institutions in Ireland have interpreted Learning for Life and other policy documents in their own policies and practice. I was also interested in investigating the barriers that were perceived to exist by people, in both government and educational institutions, to the successful implementation of lifelong learning policy in Ireland. The thesis also explores the approach that has been taken to lifelong learning in Ireland analysing whether this approach has taken a predominantly human or social capital approach or a mixture of both. Although a number of studies have investigated the impact of lifelong learning policies on national and institutional practice in other countries, very little research has been carried out on Ireland. This thesis makes a valuable contribution by providing a case study based analysis of policy development within a changing economic and social context. It also provides an insight into the approach taken by one individual country and the influences on that approach. Although the study is clearly and deliberately a case study I have included reference to two other European nations who have high adult participation rates in education, Denmark and Sweden, as comparators with the experiences of Ireland.